A Concise and Comprehensive Description of Shoulder Pathology and Procedures: The 4D Code System - Laurent Lafosse; Tom Van Isacker; Joseph B. Wilson; Lewis L. Shi (Advances in Orthopedics)
Background. We introduce a novel description system of shoulder pathoanatomy. Its goal is to provide a comprehensive three-dimensional picture, with an additional component of time; thus, we call it the 4D code. Methods. Each line of the code starts with right versus left and a time designation. The pillar components are recorded regardless of pathology; they include subscapularis, long head of biceps tendon, supraspinatus, infraspinatus, and teres minor. Secondary elements can be added if there is observed pathology, including acromioclavicular joint, glenohumeral joint, labrum, tear configuration, location and extent of partial cuff tear, calcific tendonitis, fatty infiltration, and neuropathy. Results. We provide two illustrative examples of patients which show the ease and effectiveness of the 4D code. With a few simple lines, significant amount of information about patients’ pathology, surgery, and recovery can be easily conveyed. Discussion. We utilize existing validated classification systems for parts of the shoulder and provide a frame work to build a comprehensive picture. The alphanumeric code provides a simple language that is universally understood. The 4D code is concise yet complete. It seeks to improve efficiency and accuracy of the communication, documentation, and visualization of shoulder pathology within individual practices and between providers.